Использование пьезоэлектрических материалов в качестве альтернативных источников энергии - Богдан, Ю. И. (ХНУРЭ, 2012)
This work considers the possibility of using materials with piezoelectric properties as alternative energy sources. The efficiency of piezoelectrics, depending on the material and design, has been analyzed.
Keywords: пьезоэлектрические материалы; альтернативные источники энергии